THE SPECTROPHOTOMETRIC OBSERVATIONS OF THE SUNSPOTS - U. P. Ibragimowa; D. K. Dzhumabaewa; K. K. Dzhumabaewa; M. P. Ibragimowa (Современная наука и инновации, 2022)
Observing sunspots and studying their magnetic fields is one of the daily tasks of modern heliophysics. At the end of the 19th century, Pieter Zeeman conducted a series of experiments to experimentally test whether atoms have magnetic properties. Thus, in 1896, the existence of the splitting effect of spectral lines emitted by atoms of a substance located in an external magnetic field was unambiguously confirmed for the first time. Subsequently, this phenomenon was called the Zeeman effect. This method is based on the principle of observation of magnetic fields on the Sun, in particular for the study of magnetic fields of sunspots.